Faktor-Faktor yang Mempengaruhi Kinerja Kontraktor di Padang Pariaman - Amijaya, Tisna; Hasan, Alizar; Anif, Bahrul (Universitas Batanghari, 2025)
In an interview with the field supervisor and technical implementing officers of activities involved in the implementation of construction work in the Public Works and Spatial Planning Agency of Padang Pariaman Regency, the current condition of small-qualified construction service providers tends to have weaknesses in management, mastery of technology, capital and limited experts and skilled workers so that it affects product quality, punctuality of implementation and efficiency of human resource utilization, and capital. The purpose of the study was to identify factors that influence the performance of small-qualified construction service companies in Padang Pariaman Regency and their dominant factors. The research method used is a qualitative quantitative method by distributing questionnaires to respondents, where the non-probability sampling method (no-random sample) was used in taking respondent samples. The results of the questionnaire were processed using SPSS factor analysis. The results of the study found 5 factors that influenced the performance of small-qualified construction service companies in Padang Pariaman Regency, namely managerial/organizational factors, external factors, equipment factors, economic factors, and human resource factors. The dominant factors that influenced the performance of contractors in Padang Pariaman Regency were managerial and technical factors with a % of variance value of 14.404%.